A GAP ANALYSIS OF ANTIVENOM AVAILABILITY AND ITS IMPACT ON SNAKEBITE MORTALITY IN INDONESIA - Ahmad Harits Fitra Mauladi; Kadek Karang Agustina (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Snakebite envenoming is a significant neglected tropical disease in Indonesia, characterized by high incidence and mortality. This literature review aims to analyze the gap in antivenom availability and its impact on snakebite mortality in Indonesia. This study employs a systematic literature review methodology, synthesizing data from scientific journals, government reports, and news media. The results indicate a critical public health crisis driven by several interconnected factors. First, there is a severe discrepancy between Indonesia's high venomous snake biodiversity (77 species) and the extremely limited coverage of its nationally produced antivenom, Serum Anti Bisa Ular (SABU), which is only effective against three species. Second, scientific analysis reveals that SABU has suboptimal purity and neutralization potency, even against its target venoms, necessitating larger doses and increasing the risk of adverse reactions. Third, systemic barriers, including a lack of reliable epidemiological data, a fragmented distribution chain concentrating antivenom in urban centers, widespread public misinformation about first aid, and inadequate healthcare worker training, create a broken